An Evaluation of Child Welfare Schemes for Differently-Abled Children Implemented by Chennai Corporation: Accessibility, Awareness and Impact - S. Ravichandran, S. Ravichandran; R. Premalatha, R. Premalatha (Journal of Neonatal Surgery, 2025)
The welfare and development of differently-abled children remain a critical area of focus in India’s inclusive growth agenda. In urban settings like Chennai, the Corporation of Chennai has implemented several child welfare schemes aimed at addressing the educational, medical, and social needs of children with special needs. This study evaluates the accessibility, awareness, and overall impact of these welfare schemes specifically designed for differently-abled children under the purview of the Chennai Corporation. The research adopts a mixed-method approach, combining qualitative interviews with caregivers and service providers and quantitative surveys conducted across selected urban zones within the city. The study investigates key schemes such as inclusive education programs, health screening initiatives, financial support, and early intervention services. Findings reveal that while the schemes have the potential to enhance the quality of life of differently-abled children, significant challenges persist in terms of accessibility to resources, infrastructural inadequacies, shortage of trained personnel, and limited awareness among beneficiaries. Additionally, bureaucratic delays and lack of coordinated service delivery often hinder the timely implementation of benefits. The study highlights a disparity between policy intent and on-ground realities. While some parents and caregivers reported satisfaction with specific interventions like mobile therapy units and special education services, many expressed concerns over inconsistent service delivery and lack of follow-up support. It was also observed that awareness about the availability of schemes is relatively low, particularly among marginalized and economically weaker sections. Based on the findings, the research proposes actionable recommendations including community-level awareness campaigns, digital accessibility portals, strengthening school infrastructure, and improving inter-departmental coordination. The study concludes that a more inclusive and participatory framework is essential for ensuring that welfare schemes reach every differently-abled child in Chennai.